Cyclic di-AMP as endogenous adjuvant enhanced BCG-induced trained immunity and protection against Mycobacterium tuberculosis in mice - Ning, Huanhuan; Kang, Jian; Lu, Yanzhi; Liang, Xuan; Zhou, Jie; Ren, Rui; Zhou, Shan; Zhao, Yong; Xie, Yanling; Bai, Lu; Zhang, Linna; Kang, Yali; et al. (Frontiers in Immunology, 2022)
Bacillus Calmette-Guerin (BCG) is a licensed prophylactic vaccine against tuberculosis (TB). Current TB vaccine efforts focus on improving BCG effects through recombination or genetic attenuation and/or boost with different vaccines. Recent years, it was revealed that BCG could elicit non-specific heterogeneous protection against other pathogens such as viruses through a process termed trained immunity. Previously, we constructed a recombinant BCG (rBCG-DisA) with elevated c-di-AMP as endogenous adjuvant by overexpressing di-adenylate cyclase of Mycobacterium tuberculosis DisA, and found that rBCG-DisA induced enhanced immune responses by subcutaneous route in mice after M. tuberculosis infection. In this study, splenocytes from rBCG-DisA immunized mice by intravenous route (i.v) elicited greater pro-inflammatory cytokines response to homologous and heterologous re-stimulation than BCG. After M. tuberculosis infection, rBCG-DisA immunized mice showed hallmark responses of trained immunity including potent pro-inflammatory cytokines response, enhanced epigenetic changes, altered lncRNA expressions and metabolic rewiring in BMs and tissues. Moreover, rBCG-DisA immunization induced higher antibodies and T cells in spleen and lung of mice after M. tuberculosis infection. It was found that rBGC-DisA resided longer than BCG in lung of M. tuberculosis infected mice, implying prolonged duration of vaccine efficacy. Then, we found that rBCG-DisA boosting could prolong survival of BCG-primed mice over 90 weeks against M. tuberculosis infection. Our findings provided in vivo experimental evidences that rBCG-DisA with c-di-AMP as endogenous adjuvant induced enhanced trained immunity and adaptive immunity. What’s more, rBCG-DisA showed a promising potential in prime-boost strategy against M. tuberculosis infection in adult mice.